2017
DOI: 10.1080/23802359.2017.1407707
|View full text |Cite
|
Sign up to set email alerts
|

The complete mitochondrial genome and phylogenetic analysis of Haemaphysalis longicornis Neumann (Acari: Ixodidae)

Abstract: Haemaphysalis longicornis ticks are vectors or reservoirs of numerous infectious pathogens and cause a variety of human and animal diseases worldwide. However, there is limited knowledge on available genetic sequence. Herein, we extracted the complete mitochondrial genome (mitogenome) from enriched mitochondria of H. longicornis first time in ticks and gained its sequence with 14,718bp in length. The mitogenome consisted of 13 PCGs, 22 tRNA, 2 rRNA, and 2 noncoding regions. Also, the monophyletic phylogenetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 10 publications
4
7
0
Order By: Relevance
“…As shown in Figure 1, this phylogeneric tree demonstrates three isolates of H. flava, regardless of host origins and locations, clustered together and formed a monophyletic relationship with Haemaphysalis japonica in the genus Haemaphysalis, with 100% bootstrap confidence, supporting their species validity among the family Ixodidae. In addition, within this topology, each sister genus Amblyomma, Bothriocroton, Dermacentor, Rhipicephalus or Aponomma was also treated as a monophyletic group in Ixodidae, consistent with recent molecular studies (Burger et al 2013;Geng et al 2017;Tian et al 2019). In conclusion, the complete mtDNA of H. flava sequenced here provides novel molecular evidence for phylogenetic and taxonomic position of this tick species.…”
supporting
confidence: 86%
“…As shown in Figure 1, this phylogeneric tree demonstrates three isolates of H. flava, regardless of host origins and locations, clustered together and formed a monophyletic relationship with Haemaphysalis japonica in the genus Haemaphysalis, with 100% bootstrap confidence, supporting their species validity among the family Ixodidae. In addition, within this topology, each sister genus Amblyomma, Bothriocroton, Dermacentor, Rhipicephalus or Aponomma was also treated as a monophyletic group in Ixodidae, consistent with recent molecular studies (Burger et al 2013;Geng et al 2017;Tian et al 2019). In conclusion, the complete mtDNA of H. flava sequenced here provides novel molecular evidence for phylogenetic and taxonomic position of this tick species.…”
supporting
confidence: 86%
“…Building on a concatenated amino acid dataset of 12 protein-coding genes from H. hytricis and 20 other ticks, the maximum-likelihood (ML)-based phylogeny demonstrated that two isolates of H. hytricis, regardless of host origins and locations, clustered together and were more closely related to Haemaphysalis longicornis than to other ticks in the genus Haemaphysalis, with 100% bootstrap confidence (Figure 1), supporting their species validity among the family Ixodidae. In addition, the sister genera including Archaeocroton, Bothriocroton, Dermacentor, and Rhipicephalus in this topology were treated as monophyletic relationships with Haemaphysalis in Ixodidae, consistent with recent molecular studies (Burger et al 2013;Geng et al 2017;Tian et al 2019). Taken together, the H. hytricis mitogenome data sequenced here provides a novel data resource for genetic and evolutionary biological studies of Haemaphysalis ticks.…”
supporting
confidence: 84%
“…Building on a concatenated amino acid sequences of 13 protein-coding genes from H. longicornis and 29 other ticks, the maximum-likelihood (ML)-based phylogeny demonstrated that four isolates of H. longicornis, regardless of host origins or locations, clustered together and shared a more close relationship to Haemaphysalis hystricis than to other Haemaphysalis ticks, with 100% bootstrap confidence ( Figure 1), supporting their species validity in the subfamily Haemaphysalinae. In addition, the genera including Archaeocroton, Bothriocroton, Dermacentor, Rhipicephalus, Amblyomma and Aponomma were treated as monophyletic relationships with Haemaphysalis in the family Ixodidae, agreement with recent molecular studies (Burger et al 2013;Geng et al 2017;Tian et al 2019;Liu et al 2020). In summary, the H. longicornis mitogenome sequenced here provides novel insights into genetic and phylogenetic studies of this tick.…”
supporting
confidence: 88%